Tinjauan Yuridis Perjanjian Pengikatan Jual Beli atas Objek Hak Tanggungan yang masih terikat di Bank - Lily Lee (Journal of Law and Policy Transformation, 2019)
A very important role of a bank as a business entity is a bank that has the function to raise funds from the public in the form of deposits and channel the funds raised to the public. After granting funds from the Bank to the debtor, the next issue of concern is the extraction of funds that have been disbursed through bank credit. Not all credit disbursements can be paid off by the debtor, so often the debtor takes unilateral actions by transferring the loan repayment obligation to a third party without the bank's knowledge. In order to answer the problems in this study, the author uses a type of normative research supported by primary data obtained by the author from interviews with various sources. The intent and purpose to be achieved by the author in this study is the validity of the binding agreement on the sale and purchase of object mortgage rights that are still bound in the bank. Making the Sale and Purchase Agreement by the parties alone has no impact at all on the position of ownership rights on the goods traded. The right to land has not been transferred to the buyer, even though the price has been paid, because the ownership rights to the land have only been transferred to the owner if what has been called juridical delivery. All forms of land rights transfer must be made in an authentic deed. All acts of sale on the object of Underwriting Rights that are not in accordance with the procedure cause the legal act is null and void. This is in line with the provisions of Article 20 paragraph 4 of the Underwriting Rights Act. Therefore, the position of making a binding agreement on buying and selling is not binding legal force